WORK AS A HUMAN RIGHT: A DEFENSE OF THE IMPRESCRIPTIBILITY OF DECENT WORK - Rodrigues Portelinha da Silva, João (Revista Gênero e Interdisciplinaridade, 2025)
This article proposes the incorporation of decent work into the essential core of human rights, based on the principle that the dignity of the human person is the purpose and foundation of all rights. It is argued that, while the Brazilian legal system allows for the statute of limitations on labor rights, this limitation contradicts the imprescriptible nature of human rights. Thus, decent work should be understood not only as a social right, but as a fundamental human right, the violation of which constitutes a direct offense to human dignity itself. Human Rights in the Brazilian Constitution have a hermeneutical elevation in relation to other articles of the Constitution. One of the characteristics is that they do not prescribe. If work is part of the list of Human Rights, it will logically have the same characteristics as the other human rights.